On the Denseness of Subspaces of Analytic Vectors of a Closed Linear Operator in a Banach Space - Mokrousov, Yu. G. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish conditions for the behavior of the resolvent and the location of the spectrum of a linear closed operator A densely defined in a Banach space E under which its Gevrey spaces G (β)(A), β < 1, are dense in E.